(untitled) (Journal of Engineering Science, 2022)
A degenerate quantum plasma system (DQPS) consisting of arbitrary number of degenerate light (electron, proton, neutron, etc.) and heavy (light nuclei/element, heavy nuclei/element, etc.) particle species is considered to investigate the spherically symmetric perturbation (both linear and nonlinear) of self-gravitational field. The fundamental characteristics (amplitude, width, etc.) of small amplitude self-gravitational potential structures, which are found to be formed in the considered plasma system, are examined by the reductive perturbation technique. The derivation and numerical analysis of the modified Korteweg-de Vries (mKdV) equation are obtained. The analytical results are applied in astrophysical compact objects like white dwarfs and neutron stars, which are the examples of DQPS. Journal of Engineering Science 13(1), 2022, 97-104